Gastric Lipoma (Journal of Surgical Sciences, 2019)
Lipoma, a universal tumor of adult fat cells is usually encountered in the subcutaneous plane. However no part of human body is spared of having lipomas. Gastrointestinal lipomas though rare, may prove to be more dangerous and needs special attention for diagnosis and treatment. Here, we report a 55 year old female with gastric lipoma who presented with upper abdominal pain, dyspepsia and acute upper gastrointestinal bleeding.Journal of Surgical Sciences (2014) Vol. 18 (2) : 74-77